Teachers’ questioning practices in Malaysian secondary English language classrooms / Tan Shin Yen - Tan, Shin Yen (2017)
The purpose of this study is to examine teachers’ questioning practices in Malaysian secondary English language classrooms as well as how these practices influence classroom discourse. While there have been numerous studies on various dimensions of questioning, most have focused on the investigation of individual dimensions; there has been little attention dedicated to examining the interplay between dimensions. Other than this, classroom data on questioning and classroom discourse, particularly video data in English language classrooms has been insufficient. This is even more so in the Malaysian context, where studies on questioning and classroom discourse especially at the broader level are harder to come by. Such data will be important to inform change and improvement efforts for teaching and learning. Fundamentally, this study is driven by two research questions: (1) What are teachers’ questioning practices in terms of three dimensions of questioning: types of questions, wait time, and reaction moves?; and (2) How does the interplay between these aforementioned dimensions of questioning influence classroom discourse? In this study, classroom discourse was examined through the lens of Bakhtin’s notion of dialogism. To answer the research questions of this study, a video study design was used. A random sampling of 17 schools out of almost 2,000 national secondary schools was done to obtain a representative sample of this population. From these randomly selected schools, 31 video recordings of lessons from 31 teachers teaching Form One English Language were examined. In total, about 1,514 minutes of video data were analyzed. This study found out that teachers generally used questioning practices which were often associated with monologic classroom discourse, i.e. the dominant use of display questions and short wait time, as well as the use of reaction moves such as ‘wait out/ignore’, ‘give answer’, and ‘impose’. Teachers’ questioning practices which were usually associated with dialogic classroom discourse were also discovered, but discourses never became dialogic. With further analysis on the interplay between dimensions, an overarching continuum of monologicality emerged, comprising three variations of monologicality: teacher-dominated classroom discourse, IRE-structured classroom discourse, and extended classroom discourse. There was practically no opportunity provided for interactions of multi-voices and for students to influence classroom discourse. Opportunities for student thinking and student voice were provided but within the rigid facilitation of teachers, characterized by a strong commitment to answers, low expectations of discourses, and a constant control on discourses. The findings of this study suggest a continuum-based and more nuanced conception of monologicality, where nurturing dialogicality is not a mere issue of strategy use.